Supporting the Development of Competences Necessary for the Independent Living of People With Profound Disorders of Intellectual Development: An Empirical Study - Ewelina Sobocha; Małgorzata Pietrzak (Ignatianum University Press, 2023)
Objectives of the research: The goal of the research was to identify the type and extent of activities that special education facilities engage in to teach and promote independence in people with profound disorders of intellectual development. Research methods: Empirical material was collected using the author's original online questionnaire, which consisted of 30 questions measuring the extent to which students' needs for developing independent living skills are met. The survey was conducted among special education teachers (N=642) from seven European countries (Portugal, Spain, Belgium, Poland, Bulgaria, Romania, and Turkey). A short description of the context of the issue: Independent living is widely seen as an immanent attribute of adulthood. Children and adolescents are prepared for independent living through the process of upbringing and socialization; people with disabilities are additionally prepared through rehabilitation. For people with a profound disorder of intellectual development, independent living is challenging but possible with the right support. Research findings: The results indicate that in the course of developing independent living skills in people with profound disorders of intellectual development, efforts are mainly made to improve their self-management skills and democratic management methods in both team work and individual work. Conclusions and recommendations: In the surveyed countries, there is a tendency to limit work for developing independent living skills to a single type of intervention. Rarely are two or three methods - not to mention four - simultaneously used to stimulate the development of independent living skills. It is therefore necessary to call for increased efforts to promote independent living among people with profound disorders of intellectual development and to focus this support on autonomy, self-determination, achieving quality of life goals, and, above all, the ability to make decisions - since this is what determines true independence in life.